Open bite treatment in mixed dentition with SN6 device (Research, Society and Development, 2021)
Open bite is defined as the absence of contact between the incisors in maximum habitual intercuspation, characterizing a negative goodwill. That requires early treatment so that bone-based changes do not settle in the stomatognathic system. The purpose of this study was to describe the applicability of the functional aspect of Maxillary Orthopedics in a nine-year-old female child, during the mixed dentition period. Assisted at the Dental School-School of UFPE, in Recife, and diagnosed with an anterior skeletal open bite. The results were achieved in the interval of thirty months of treatment, using the Simões Network 6 (SN6) device - special model of lip shields. The intervention with the use of the device defines that the technique used made possible the expansion of the dental arches and the anterior rotation of the mandible. There was a change in posture, with the closure of the anterior open bite and sealing lip. After rehabilitation of malocclusion, thanks to the patient's collaboration, with the constant use of device, facial harmony has been restored, as well as functionality typical of the stomatognathic system - conquest of normal swallowing, lip sealing and nasal breathing.